Factors affecting work-related stress of office staff in small manufacturing enterprises in Klang - Kiat Keng, Lee (2014)
As is known that Work-related stress has an impact on the overall functioning of companies, work-related stress is becoming an increasingly important issue in a competitive business environment for companies. This study aims to identify the factors that inﬂuence Work-related stress of ofﬁce staff in small manufacturing enterprises in Klang. Five factors, namely workload, role ambiguity, role conﬂict, supervisor support and interpersonal relationship would inﬂuence work-related stress of ofﬁce staff were focused and investigated. Quantitative methods were used to collect and analyse data. 50 participants participated in the questionnaire survey. Results indicated that there are statistically signiﬁcant relationships between Work-related stress and four factors, which are Workload, role conﬂict, supervisor support and interpersonal relationship. Role ambiguity was found having no statistically signiﬁcant relationship with work-related stress. The ﬁndings of this study could contribute to the current and fut1.u'e generations’ knowledge of the work-related stress, and its impact on companies